An Analytical Study of the Names and Honorific Titles of Prophet Muhammad (PBUH) in the Poetry of Ustad Khalilullah Khalili - Mohammad Nasir Zarifi (CV. Abhinaya Indo Group, 2025)
In contemporary Afghan poetry, the invocation of divine figures, particularly Prophet Muhammad Mustafa (PBUH), reflects both deep spiritual devotion and the preservation of cultural-religious identity. Ustad Khalilullah Khalili, one of Afghanistan’s most celebrated poets, frequently incorporates the images and names of prophets in his works, with the Prophet of Islam occupying a central and honored position. This study employs an analytical–descriptive method, examining Khalili’s Divan alongside relevant literary and scholarly sources, to investigate how the Prophet is represented and under which names, titles, and attributes. The analysis reveals that Khalili portrays the Prophet as a multifaceted figure spiritual guide, moral exemplar, source of divine light, and symbol of compassion and justice. His poetry utilizes various literary devices, including metaphors, similes, Qur’anic allusions, imagery, and intertextual references, to emphasize the Prophet’s ethical, spiritual, and social significance. Furthermore, recurring themes such as devotional love (Ishq-e-Nabawi), prophetic miracles, mercy, and guidance reinforce the Prophet’s enduring relevance in contemporary Afghan literary culture. The study concludes that Khalili’s work not only reflects his personal devotion and mastery of classical Persian poetic tradition but also bridges classical literary heritage with modern Afghan sensibilities. Prophetic imagery in his poetry thus serves as a living source of aesthetic inspiration, moral reflection, and spiritual guidance.